Impact of COVID-19 on healthcare and livelihood of tribals in Odisha - Panda, Sanghamitra (International Journal Of Community Medicine And Public Health, 2022)
Odisha, one of the front runners among the states in India has been fighting COVID-19 pandemic. To curb the pandemic, many state governments including Odisha have been implementing lockdown and different restrictions at different times. This pandemic is heavily impacting the precious lives and livelihood of human beings across the globe. But this impact is pronounced for the people who live in forests and hill areas mainly- Tribal because of remoteness, ineffective planning and execution from government bodies. So, the lives of tribal are getting worse in passing days in terms of livelihood and health care issues. In addition, the restrictions and lockdown imposition to curb the infection has deteriorated the livelihood of the tribal further. This paper outlines in detail about the impact of COVID-19 in terms of health care issues and livelihood of tribal in Odisha since the outset of the pandemic in early 2020 till date. One new solution is proposed to improve the supply chain system so that the tribal products; agriculture, artefacts, minor forest products (MFPs) can be sold without much hurdle and waiting to improve the livelihood of Tribal. Few steps are also proposed to improve the health of Tribal.